Mass scales and stability of the proton in [SU(6)]3 X Z3 (1994)
ABSTRACT: We prove that the proton is stable in the gauge model [SU(6)] x Zs which uni6es nongravitational forces with Savors, broken spontaneously by a minimal set of Higgs fields and vacuum expectation values down to SU(3)cU(1)aM. We also compute the evolution of the gauge coupling constants and show how agreement with precision data can be obtained.